Depression - Breznoščáková, Dagmar (IntechOpen, 2017)
Depressive disorders can be seen as a disturbance to the balance of mind and body. Because it is a mental disorder and psychiatry is a branch of medicine, the question how mind and body interact in depression should be treated as a medical rather than metaphysical mind-body problem. The relation between mind and body as it pertains to this illness should be construed in teleological rather than causal terms. Mental states like beliefs and emotions serve an adaptive purpose by constraining the physiologic systems involved in the body's stress response, thus preserving homeostasis and protecting us from various disorders. Depression results when the mind fails its constraining role.